THE IMAGE OF CONTEMPORARY JAPAN FROM THE PERSPECTIVE OF INDONESIAN VISITOR - Widiyanto, Nur; Atiqah, Annissa Nurul (Kepariwisataan: Jurnal Ilmiah, 2023)
AbstractBefore the outbreak of the Pandemic Covid-19, together with a better economic and political relationship between Indonesia and Japan, the number of Indonesian visitors to Japan for several different purposes has significantly increased and vice versa. It has opened a bigger opportunity for the development of cultural understanding to each other through more intensive direct encounters and people-to-people direct communication, both in Japan and Indonesia.  The article focuses on describing the image of contemporary Japan from the point of view of the Indonesian visiting Japan. Employing a qualitative approach through serial fieldwork in Hokkaido and Tokyo, research findings show that witnessing the daily behavior of the Japanese in their home country and directly interacting with the host community through tourism grounds have shaped a new better image of contemporary Japan and the Japanese. It proves the role of tourism in increasing the better cultural understanding between two different cultural groups, including those inheriting a bitter memory from a particular conflict in the past. AbstrakSebelum merebaknya Pandemi Covid-19, seiring dengan hubungan politik serta ekonomi yang lebih baik antara Indonesia dengan Jepang, jumlah kunjungan dari Indonesia ke Jepang untuk berbagai tujuan meningkat secara signifikan, begitu pula sebaliknya, dari Jepang ke Indonesia. Hal ini telah membuka kesempatan untuk terbentuknya suatu pemahaman budaya yang lebih baik diantara satu sama lain sebagai hasil dari interaksi langsung yang terjadi, baik di Jepang maupun di Indonesia.  Artikel ini berfokus untuk menggambarkan bagaimana citra Jepang kontemporer dari orang Indonesia yang berkunjung ke Jepang. Dengan menggunakan pendekatan kualitatif melalui penelitian lapangan di Hokkaido dan Tokyo, temuan penelitian menunjukkan bahwa melihat perilaku sehari-hari orang Jepang di negara asalnya serta berinteraksi langsung khususnya melalui berbagai kegiatan yang terkait pariwisata dengan tuan rumah telah membentuk citra yang lebih baik tentang Jepang dan orang Jepang di masa kini. Hal ini membuktikanbagaimana peran penting pariwisata dalam meningkatkan pemahaman budaya yang lebih baik antara dua kelompok budaya yang berbeda, termasuk mereka yang mewarisi konflik di masa lalu.